A dual-curing anti-corrosion coating for battery box and preparation method thereof

By introducing thermal curing components into the UV curing system, the anticorrosion coating of the battery box can be double cured, which solves the problem of long curing time, improves production efficiency, and improves the adhesion and impact resistance of the coating.

CN116731573BActive Publication Date: 2025-03-07GUANGDONG HEYGEY LIGHT CURING MATERIALS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310726509.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2025-03-07
Estimated Expiration
2043-06-19

AI Technical Summary

Technical Problem

In the prior art, the anticorrosion coating on the surface of the battery box has a long curing time, resulting in low production efficiency and cannot meet the production needs of power batteries.

Method used

Introducing components that can be heat-cured in the UV curing system enables anticorrosion coatings to be cured through the dual UV-thermal curing method, shortening curing time and improving production efficiency.

Benefits of technology

Through the dual curing method, the curing time is shortened from 30 minutes to 10-15 minutes, which improves production efficiency and enhances the adhesion, flexibility and impact resistance of the anticorrosion coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004293031340000021
    Figure BDA0004293031340000021
  • Figure BDA0004293031340000041
    Figure BDA0004293031340000041
  • Figure BDA0004293031340000071
    Figure BDA0004293031340000071
Patent Text Reader

Abstract

The invention provides a dual-curing anti-corrosion coating for a battery box and a preparation method thereof, and relates to the technical field of coatings. The anti-corrosion coating, through the synergistic effect of a component A and a component B, introduces a component that can be heat-cured into a UV curing system, so that the anti-corrosion coating can be cured by a dual UV-heat curing method, thereby shortening the curing time and improving the production efficiency, thereby solving the problem of a long curing time of the anti-corrosion coating on the surface of the battery box in the prior art. On the other hand, through the synergistic effect of the components in the system, not only is there excellent adhesion between the prepared anti-corrosion coating and an aluminum alloy battery box, but the shrinkage rate of the system can also be reduced, the flexibility of the anti-corrosion coating can be improved, and the impact resistance of the coating can be greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of coating technology, and in particular to a dual-curing anti-corrosion coating for a battery box and a preparation method thereof. Background Art

[0002] With the development of new energy vehicles, the demand for power batteries, as one of the main components of new energy vehicles, will increase sharply in the future.

[0003] Currently, power batteries used in electric vehicles mostly use integrated aluminum alloy battery cases. In order to enhance the corrosion resistance of aluminum alloy battery cases, the conventional process is to spray amino anti-corrosion coatings on their surface. However, this process requires baking at a temperature of 150°C or above for more than 30 minutes to cure, resulting in low production efficiency and cannot meet the current production needs of power batteries. Summary of the invention

[0004] The technical problem to be solved by the present invention is: in order to solve the problem of long curing time of anti-corrosion coating on the surface of battery box in the prior art, the present invention provides a dual-curing anti-corrosion coating for battery box, which introduces components that can be heat-cured into the UV curing system, so that the coating can be cured by a dual method of UV-heat curing, thereby shortening the curing time and improving production efficiency, thereby solving the problem of long curing time of anti-corrosion coating on the surface of battery box in the prior art.

[0005] The technical solution adopted by the present invention to solve its technical problem is:

[0006] A dual-curing anti-corrosion coating for a battery box, comprising a component A and a component B;

[0007] In parts by weight, component A includes the following components:

[0008]

[0009] In parts by weight, component B includes the following components:

[0010] 50-70 parts of polyurethane acrylic resin containing isocyanate group;

[0011] 30-50 parts of anhydrous n-butyl acetate.

[0012] Optionally, the mass ratio of the component A to the component B is 10:1.

[0013] Optionally, the hydroxyl content of the hydroxyl-containing polyurethane acrylic resin is 100-120 mg / KOH.

[0014] Optionally, the solvent is selected from at least one of ethylene glycol monobutyl ether, propylene glycol methyl ether acetate, mixed dibasic acid, propylene glycol methyl ether, and isobutyl isobutyrate.

[0015] Optionally, the dispersant is selected from at least one of a polymer copolymer dispersant and a structured acrylic copolymer dispersant.

[0016] Optionally, the anti-corrosion pigment filler is selected from at least one of titanium dioxide, carbon black, mica powder, barium sulfate, zinc phosphate, aluminum tripolyphosphate, and talc.

[0017] Optionally, the initiator is selected from at least one of 2,2-dimethyl-2-hydroxyacetophenone, 1-hydroxycyclohexyl benzophenone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2,4,6-trimethylbenzoylphosphonic acid ethyl ester, phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone and isopropylthioxanthone.

[0018] Optionally, the leveling agent is selected from at least one of silicone-based polydimethylsiloxane, polyester-modified silicone, polyether-modified silicone, alkyl-modified silicone, and fluorine-modified acrylate.

[0019] Optionally, the mass content of -NCO in the isocyanate-containing polyurethane acrylic resin is 10%-15%.

[0020] Another object of the present invention is to provide a method for preparing the dual-curing anti-corrosion coating for a battery box as described above, comprising the following steps:

[0021] S1: under the condition of shielding ultraviolet rays, add phosphate modified acrylic resin, solvent-based polyurethane resin, hydroxyl polyurethane acrylic resin, solvent and dispersant in a stirring tank in order according to the formula amount, stir evenly at a speed of 800 rpm, add anticorrosive pigment and filler while stirring, increase the speed to 2500-3500 rpm after adding, disperse for 30 minutes, test the fineness of the system with a scraper fineness meter, stop high-speed dispersion when the fineness of the system is less than 10 microns, add initiator and leveling agent to the stirring tank, disperse for 10 minutes at a speed of 1000 rpm, and prepare component A;

[0022] S2: Under the condition of shielding from ultraviolet rays and controlling the humidity below 60%, add isocyanate-containing polyurethane acrylic resin and anhydrous n-butyl acetate into a stirring tank in sequence according to the formula, and stir at a speed of 500 rpm for 10 minutes to obtain component B.

[0023] The beneficial effects of the present invention are:

[0024] The dual-curing anti-corrosion coating for the battery box provided by the present invention, on the one hand, introduces a component that can be heat-cured into the UV curing system, so that the anti-corrosion coating can be cured by a dual method of UV-heat curing, thereby shortening the curing time and improving production efficiency, thereby solving the problem of long curing time of the anti-corrosion coating on the surface of the battery box in the prior art; on the other hand, through the synergistic effect of the components in the system, not only is there excellent adhesion between the prepared anti-corrosion coating and the aluminum alloy battery box, but the shrinkage rate of the system can also be reduced, the flexibility of the anti-corrosion coating can be improved, and the impact resistance of the coating can be greatly improved. DETAILED DESCRIPTION

[0025] The present invention is now further described in detail. The embodiments described below are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention belong to the scope of protection of the present invention.

[0026] In order to solve the problem of long curing time of anti-corrosion coating on the surface of battery box in the prior art, the present invention provides a dual-curing anti-corrosion coating for battery box, including component A and component B; component A includes the following components in parts by weight:

[0027]

[0028] In parts by weight, component B includes the following components:

[0029] 50-70 parts of polyurethane acrylic resin containing isocyanate group;

[0030] 30-50 parts of anhydrous n-butyl acetate.

[0031] The UV curing system has the advantages of fast curing and high solid content. It can achieve 100% solid content according to construction requirements. The system has a large cross-linking density after curing, which makes the prepared coating have the characteristics of high hardness and good chemical resistance. However, since the power batteries of electric vehicles have high requirements for corrosion resistance, a large amount of inorganic anti-corrosion fillers need to be introduced into the anti-corrosion coating system used for electric vehicle power batteries, resulting in a thicker film thickness. In the case of high film thickness, it is difficult for a pure UV curing system to effectively cure the interior, affecting the physical and chemical properties of the anti-corrosion coating.

[0032] The dual-curing anti-corrosion coating for the battery box provided by the present invention, on the one hand, introduces a component that can be heat-cured into the UV curing system, so that the anti-corrosion coating can be cured by a dual method of UV-heat curing, thereby shortening the curing time and improving production efficiency, thereby solving the problem of long curing time of the anti-corrosion coating on the surface of the battery box in the prior art; on the other hand, through the synergistic effect of the components in the system, not only is there excellent adhesion between the prepared anti-corrosion coating and the aluminum alloy battery box, but the shrinkage rate of the system can also be reduced, the flexibility of the anti-corrosion coating can be improved, and the impact resistance of the coating can be greatly improved.

[0033] The dual-curing anti-corrosion coating for the battery box provided by the present invention can fully cure the inside of the system by thermal curing when UV curing cannot penetrate the film thickness. At the same time, through the dual curing method, the curing time of the anti-corrosion coating of the aluminum alloy battery box can be shortened from 30 minutes to 10-15 minutes, thereby greatly improving the production efficiency of power batteries and helping them to meet the current production needs of power batteries.

[0034] In order to take into account both the curing efficiency and the performance of the anti-corrosion coating, the present invention preferably has a mass ratio of component A to component B of 10:1.

[0035] Specifically, in the present invention, the preferred phosphate-modified acrylic resin is selected from at least one of Changsha Jingtuan J9082, Guangzhou Bahe BW8070, Guangzhou Bahe BW8071, and Zhongshan Ketian 7113; the preferred solvent-based polyurethane resin is selected from at least one of Zhuhai Changxing 6071, Zhuhai Changxing 6063, and Shanghai Santong ST165.

[0036] The hydroxyl content of the hydroxyl-containing polyurethane acrylic resin of the present invention is preferably 100-120 mg / KOH, and is further preferably selected from at least one of Guangzhou Bahe BW8211 and Guangzhou Bahe BW8214.

[0037] The preferred solvent of the present invention is a high boiling point solvent, and is further preferably selected from at least one of ethylene glycol monobutyl ether, propylene glycol methyl ether acetate, mixed dibasic acid, propylene glycol methyl ether, and isobutyl isobutyrate.

[0038] The preferred dispersant of the present invention is selected from at least one of polymer block copolymer dispersants, polymer copolymer dispersants, and structured acrylic copolymer dispersants, and is further preferably selected from at least one of BYK-168, BYK-2009, BASF EAKA4310, and Tianlong Chemical Tilosperse5048.

[0039] In the present invention, the preferred anticorrosive pigment filler is selected from at least one of titanium dioxide, carbon black, mica powder, barium sulfate, zinc phosphate, aluminum tripolyphosphate, and talc; the preferred initiator is selected from at least one of 2,2-dimethyl-2-hydroxyacetophenone (1173), 1-hydroxycyclohexyl benzophenone (184), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), 2,4,6-trimethylbenzoylphosphonic acid ethyl ester (TPO-L), phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide (819), 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone (907), and isopropylthioxanthone (ITX); and the preferred leveling agent is selected from at least one of silicone polydimethylsiloxane, polyester-modified silicone, polyether-modified silicone, alkyl-modified silicone, and fluorine-modified acrylate.

[0040] In the present invention, the mass content of -NCO in the isocyanate-containing polyurethane acrylic resin is preferably 10%-15%, and is further preferably selected from at least one of allnex EBECRYL 4141, allnex EBECRYL 4150, and Guangzhou Bahe BW8210.

[0041] Another object of the present invention is to provide a method for preparing the dual-curing anti-corrosion coating for a battery box as described above, comprising the following steps:

[0042] S1: Under the condition of shielding ultraviolet rays and using yellow light for lighting, add phosphate modified acrylic resin, solvent-based polyurethane resin, hydroxyl polyurethane acrylic resin, solvent and dispersant in the mixing tank in order according to the formula, stir evenly at a speed of 800 rpm, add anticorrosive pigment and filler while stirring, increase the speed to 2500-3500 rpm after adding, and disperse for 30 minutes, test the fineness of the system with a scraper fineness meter, stop high-speed dispersion when the fineness of the system is less than 10 microns, add initiator and leveling agent to the mixing tank, disperse for 10 minutes at a speed of 1000 rpm, and obtain component A;

[0043] S2: Under the condition of shielding from ultraviolet rays, using yellow light for lighting and controlling the humidity below 60%, add isocyanate-containing polyurethane acrylic resin and anhydrous n-butyl acetate into a mixing tank in sequence according to the formula, and stir at a speed of 500 rpm for 10 minutes to obtain component B.

[0044] The dual-curing anti-corrosion coating for battery boxes prepared by the preparation method provided by the present invention, on the one hand, introduces a component that can be heat-cured into the UV curing system, so that the anti-corrosion coating can be cured by a dual method of UV-heat curing, thereby shortening the curing time and improving production efficiency, thereby solving the problem of long curing time of the anti-corrosion coating on the surface of the battery box in the prior art; on the other hand, through the synergistic effect of the components in the system, not only the prepared anti-corrosion coating has excellent adhesion to the aluminum alloy battery box, but also the shrinkage rate of the system can be reduced, the flexibility of the anti-corrosion coating can be improved, and the impact resistance of the coating can be greatly improved.

[0045] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below.

[0046] The composition of component A in Examples 1-5 is shown in Table 1 in parts by weight:

[0047] Table 1

[0048]

[0049]

[0050] The composition of component B in Examples 1-5 is shown in Table 2 in parts by weight:

[0051] Table 2

[0052]

[0053] The composition of component A in comparative examples 1-8 is shown in Table 3 in parts by weight:

[0054] Table 3

[0055]

[0056]

[0057] The compositions of component B in Comparative Examples 1-8 are the same as that in Example 1.

[0058] The composition of component A in comparative example 9 is the same as that in example 1, and the isocyanate-containing polyurethane acrylic resin in component B is W23951 produced by Guangzhou Five Elements Material Technology Co., Ltd.

[0059] The construction methods of the above-mentioned embodiments 1-5 and comparative examples 1-9 are as follows: power battery box → dust removal → direct spraying (component A: component B, mass ratio is 10:1, spray film thickness is 50-100 microns) → infrared leveling for 3-5 minutes (temperature is 50-70°C) → UV curing (curing energy is 500-1000mJ / cm2) → thermal curing (temperature is 80-100°C) for 8-10 minutes → workpiece offline.

[0060] The compositions of component A and component B in Comparative Examples 10 and 11 are the same as those in Example 1, except that in the construction method, the mass ratio of component A to component B in Comparative Example 10 is 5:1, and the mass ratio of component A to component B in Comparative Example 11 is 15:1.

[0061] The coatings prepared in each embodiment and comparative example were tested for performance as follows:

[0062] Appearance: Determined by visual inspection.

[0063] Hardness: Measured in accordance with GB / T6739-2006.

[0064] Impact (50Kg): Impact test is carried out according to GB / T 1732-93 paint film impact resistance determination method.

[0065] Adhesion: Tested according to ASTM D3359-09 test standard.

[0066] Electrolyte resistance (24h): Soak in an electrolyte of 50% ethylene carbonate and 50% methyl carbonate for 24 hours. After 24 hours, there is no blistering or wrinkling on the board surface. Slight discoloration and gloss loss are allowed to be qualified.

[0067] Salt spray resistance (800h): Tested in accordance with GB1771 paint film neutral salt spray resistance test.

[0068] Boiling at 100℃: Boil in a 100℃ water bath for 1 hour. The board surface shall be qualified if there is no bubbling, whitening or wrinkling, and the adhesion is 4B or above.

[0069] The test results of the coatings prepared in Examples 1-5 are shown in Table 4:

[0070] Table 4

[0071]

[0072] It can be seen from the data in the above table that the anti-corrosion coating provided by each embodiment of the present invention has a short curing time, high production efficiency, and low VOC content, and is suitable for industrial production; the prepared anti-corrosion coating has excellent adhesion to the aluminum alloy surface of the power battery box, and at the same time, the anti-corrosion coating gives the power battery box better hardness, chemical resistance and impact resistance.

[0073] The test results of the coatings prepared in Comparative Examples 1-10 are shown in Table 5:

[0074] Table 5

[0075]

[0076] The difference between Comparative Example 1 and Example 1 is that no phosphate-modified acrylic resin is added, the adhesion between the prepared coating and the substrate is reduced, the hardness is reduced, and the impact resistance and chemical resistance are deteriorated.

[0077] The difference between Comparative Example 2 and Example 1 is that the amount of phosphate-modified acrylic resin added is increased, and the chemical resistance and water boiling resistance of the prepared coating are both deteriorated.

[0078] The difference between Comparative Example 3 and Example 1 is that the phosphate-modified acrylic resin is Lencolo 4051 produced by Guangdong Lancolu New Materials Co., Ltd., and the hardness of the prepared coating is reduced.

[0079] The difference between Comparative Example 4 and Example 1 is that no solvent-based polyurethane resin is added, and the chemical resistance and water resistance of the prepared coating deteriorate.

[0080] The difference between Comparative Example 5 and Example 1 is that the amount of solvent-based polyurethane resin added is increased, the surface properties of the prepared coating deteriorate, the hardness decreases, and the chemical resistance also significantly deteriorates.

[0081] The difference between Comparative Example 6 and Example 1 is that no hydroxyl-containing polyurethane acrylic resin is added, and the adhesion of the prepared coating is reduced, while the chemical resistance and water resistance are deteriorated.

[0082] The difference between Comparative Example 7 and Example 1 is that the amount of hydroxyl-containing polyurethane acrylic resin added is increased, and the chemical resistance of the prepared coating becomes poor.

[0083] The difference between Comparative Example 8 and Example 1 is that the hydroxyl-containing polyurethane acrylic resin is L-8468 produced by Guangdong Lankelu New Materials Co., Ltd., and the chemical resistance and boiling water resistance of the prepared coating are deteriorated.

[0084] The difference between Comparative Example 9 and Example 1 is that the isocyanate-containing polyurethane acrylic resin is W23951 produced by Guangzhou Five Elements Material Technology Co., Ltd., and the chemical resistance and boiling water resistance of the prepared coating are slightly reduced.

[0085] The difference between Comparative Example 10 and Example 1 is that during the construction process, the mass ratio of component A to component B is 5:1, and the water resistance of the prepared coating deteriorates.

[0086] The difference between Comparative Example 11 and Example 1 is that during the construction process, the mass ratio of component A to component B is 15:1, and the chemical resistance and water resistance of the prepared coating deteriorate.

[0087] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A dual-curing anti-corrosion coating for a battery box, characterized in that: It includes component A and component B; component A includes the following components in parts by weight: 15-25 parts of modified acrylic resin; 15-25 parts of solvent-based polyurethane resin; 8-12 parts of hydroxyl-containing polyurethane acrylic resin; 8-12 parts of solvent; Dispersant 0.5-1.5 parts; 26.7-36.7 parts of antiseptic pigments and fillers; 5-9 parts of initiator; Leveling agent 0.2-0.4 parts; In parts by weight, component B includes the following components: 50-70 parts of polyurethane acrylic resin containing isocyanate group; 30-50 parts of anhydrous n-butyl acetate; The modified acrylic resin is Changsha Jingtuan J9082; The hydroxyl-containing polyurethane acrylic resin is Guangzhou Bahe BW8211.

2. The dual-curing anti-corrosion coating for battery case according to claim 1, characterized in that: The mass ratio of the A component to the B component is 10:

1.

3. The dual-curing anti-corrosion coating for a battery case as claimed in claim 1 or 2, characterized in that: The hydroxyl content of the hydroxyl-containing polyurethane acrylic resin is 100-120 mg / KOH.

4. The dual-curing anti-corrosion coating for a battery case as claimed in claim 1 or 2, characterized in that: The solvent is selected from at least one of ethylene glycol monobutyl ether, propylene glycol methyl ether acetate, mixed dibasic acid, propylene glycol methyl ether, and isobutyl isobutyrate.

5. The dual-curing anti-corrosion coating for a battery case as claimed in claim 1 or 2, characterized in that: The dispersant is a structured acrylic copolymer dispersant.

6. The dual-curing anti-corrosion coating for a battery case as claimed in claim 1 or 2, characterized in that: The anticorrosive pigment and filler is selected from at least one of titanium dioxide, carbon black, mica powder, barium sulfate, zinc phosphate, aluminum tripolyphosphate and talc.

7. The dual-curing anti-corrosion coating for a battery case as claimed in claim 1 or 2, characterized in that: The initiator is selected from at least one of 2,2-dimethyl-2-hydroxyacetophenone, 1-hydroxycyclohexyl benzophenone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2,4,6-trimethylbenzoylphosphonic acid ethyl ester, phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone and isopropylthioxanthone.

8. The dual-curing anti-corrosion coating for a battery case as claimed in claim 1 or 2, characterized in that: The leveling agent is selected from at least one of silicone-based polydimethylsiloxane, polyester-modified silicone, polyether-modified silicone, alkyl-modified silicone, and fluorine-modified acrylate.

9. The dual-curing anti-corrosion coating for a battery case as claimed in claim 1 or 2, characterized in that: The mass content of -NCO in the isocyanate-containing polyurethane acrylic resin is 10%-15%.

10. A method for preparing a dual-curing anti-corrosion coating for a battery case as claimed in any one of claims 1 to 9, characterized in that: The steps include: S1: under the condition of shielding ultraviolet rays, add phosphate modified acrylic resin, solvent-based polyurethane resin, hydroxyl polyurethane acrylic resin, solvent and dispersant in a stirring tank in order according to the formula amount, stir evenly at a speed of 800 rpm, add anticorrosive pigment and filler while stirring, increase the speed to 2500-3500 rpm after adding, disperse for 30 minutes, test the fineness of the system with a scraper fineness meter, stop high-speed dispersion when the fineness of the system is less than 10 microns, add initiator and leveling agent to the stirring tank, disperse for 10 minutes at a speed of 1000 rpm, and prepare component A; S2: Under the condition of shielding from ultraviolet rays and controlling the humidity below 60%, add isocyanate-containing polyurethane acrylic resin and anhydrous n-butyl acetate into a stirring tank in sequence according to the formula, and stir at a speed of 500 rpm for 10 minutes to obtain component B.

Citation Information

Patent Citations

  • Dual photocurable UV (ultraviolet) paint as well as preparation method and spraying method thereof

    CN104293162A